HUBUNGAN TENAGA MEDIS DALAM INFORMED CONSENT DAN PERJANJIAN TERAPEUTIK TERHADAP PERTANGGUNGJAWABAN RUMAH SAKIT - Junaidi Junaidi (STIKes Al-Insyirah Pekanbaru, 2021)
The relationship between medical personnel, hospital and patient are known by therapeutics agreements, which are the legal relations that generate health rights and obligation. This therapeutic relationship begins with the patient’s informed assement of medical presence as well as informed consent. The underlying legal relationships between medical personnel, patient and hospital under article 1367 of the civil law code. These proposed legal relationship led to the principle of vicpredictability, where any omission or missteps of medical action committed by hospital personnel became hospital responbility. According article 46 of Law Number 44 of the year 2009 statute on hospitals determines that there is a concentrated legal responbility for any omission made by hospital personnel..